2022
DOI: 10.1186/s12877-022-02947-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of walking states, self-reported daily walking amount and age on the gait of older adults measured with a smart-phone app: a pilot study

Abstract: Background Smartphones provide a cost-effective avenue for gait assessment among older adults in the community. The purpose of this study is to explore the impact of walking state, self-reported daily walking amount, and age on gait quality, using a smartphone application. Methods One hundred older adult individuals from North China, aged 73.0 ± 7.7 years, voluntarily participated in this study. They performed three walking tests: normal walking, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…It is essential to evaluate gait variables under conditions that older adults are likely to encounter in daily activity. To date, many smartphone applications have been compared to the gold standard motion laboratory to determine basic spatiotemporal variables (e.g., cadence, speed, stride length) of walking [11][12][13][14]. However, no study has compared gait parameters beyond the basic spatiotemporal variables, including stance, step length, single and double support in various gait conditions, leaving questions to the validity and reliability of the product.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to evaluate gait variables under conditions that older adults are likely to encounter in daily activity. To date, many smartphone applications have been compared to the gold standard motion laboratory to determine basic spatiotemporal variables (e.g., cadence, speed, stride length) of walking [11][12][13][14]. However, no study has compared gait parameters beyond the basic spatiotemporal variables, including stance, step length, single and double support in various gait conditions, leaving questions to the validity and reliability of the product.…”
Section: Introductionmentioning
confidence: 99%
“…In this review, I did not find one particular smartphone set-up that was used by most studies, but a wide variety of combinations. The most used set-up was a smartphone attached to a sacroiliac belt, which was used in 8 of 11 studies screened [ 20 , 21 , 22 , 26 , 27 , 28 , 29 , 30 ]. The other position was in the pant pocket [ 14 , 23 , 25 ] ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies analyzed gait parameters collected with smartphones using descriptive statistics and ANOVA; analysis showed that age had a significant effect on smaller step frequency ( p < 0.001) [ 20 ], worse step regularity and variability [ 29 ]. Gait cadence, which is also reported as step frequency, could be a useful indicator when estimating functional capacity, with a sensitivity of 0.81 (95% CI: 0.77, 0.85) and a specificity of 0.57 (95% CI: 0.55, 0.59) [ 27 ].…”
Section: Resultsmentioning
confidence: 99%